Self-Reported Sleepiness, Fatigue and Risk of Obstructive Sleep Apnea Using the STOP BANG Components: Women’s Perspective - Jasmine M; Suganthi S; Manoj P; Divya Ilanchoorian; Vijayalakshmi (National Journal of Community Medicine, 2023)
Introduction: About 2-4% of adults have obstructive sleep apnoea (OSA), a frequent chronic condition. The disorder is characterised by recurrent bouts of whole or partial collapse of the upper airway, primarily the oropharyngeal tract, while sleeping, which results in a decrease or stoppage of airflow. The aim of the study is to assess the relationship between the self-reported sleepiness, fatigue and the risk of Obstructive Sleep Apnea among the midlife women aged 40 to 65 years Methodology: This was a cross sectional study conducted in the field practice area of rural and urban health and training centre of a tertiary care teaching hospital, Chengalpattu district, Tamilnadu among 380 women aged 40 to 65 years. Results: Mean age of the study population was 49.69 (± 11.2). On risk categorization by STOP-BANG Questionnaire, it was found that 72.9% (277), 26.1% (99) and 1.1% (4) had low, intermediate and high risk for sleep apnea. 16.9% of the study participants had excessive daytime sleepiness. Fatigue severity scale of more than or equal to 36 was seen among 34.5% of the study participants. Conclusion: The STOP-Bang questionnaire has been shown in studies to be a quick, efficient, and accurate OSA screening tool. It can make it easier to allocate resources effectively for detecting and treating OSA that had not yet been recognised.